Feeding practices in children aged 0 to 24 months (Research, Society and Development, 2022)
Food and nutrition are important conditions for the development and growth of children, allowing adequate cognitive and motor acquisitions, in addition to the formation of healthy eating habits. This research aimed to evaluate breastfeeding and complementary feeding in children from 0 to 24 months of age, assisted in Primary Health Care in the city of Bocaina/PI. The research is epidemiological, descriptive, cross-sectional with data collection that took place between October 2021 and January 2022, based on a structured online form applied to mothers registered in the Family Health Strategy. The sample consisted of 25 children, however 18 participated in this study, 72% female, 61% white, 88% were born at term, 94% had surgical delivery. Approximately 94% of the mothers had low income, with a family composition of 4 to 5 people, 33.3% with incomplete primary education and the same proportion with complete higher education. Of the 7 children aged less than 6 months, all were using breast milk, however, 28.6% drank water and tea and 28.6% infant formula. As for the 11 children aged 6 to 24 months, 54.5% consumed sugar, snacks, milk and derivatives and 63.6% received fruits as their first food and more than half 54.6% of pasty consistency. Breastfeeding was not exclusive, for children younger than 6 months, being predominant and supplemented. For children older than 6 to 24 months, the food introduction was offered with inappropriate foods, including the consumption of ultra-processed foods.